2018
DOI: 10.1038/s41598-018-21320-1
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of an extensive Acheulean large cutting tool accumulation in Europe from Porto Maior (Galicia, Spain)

Abstract: We describe a European Acheulean site characterised by an extensive accumulation of large cutting tools (LCT). This type of Lower Paleolithic assemblage, with dense LCT accumulations, has only been found on the African continent and in the Near East until now. The identification of a site with large accumulations of LCTs favours the hypothesis of an African origin for the Acheulean of Southwest Europe. The lithic tool-bearing deposits date back to 293–205 thousand years ago. Our chronological findings confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 77 publications
(105 reference statements)
10
78
0
13
Order By: Relevance
“…A multiple centre approach seems therefore indispensable when dating this type of fluvio-estuarine sediment, even when the sedimentological characteristics of the sediments seem initially quite suitable for an ESR study (as it was the case for the Tourville D1 and I units). Similar observations have been recently made on fluvial deposits from Spain (Duval et al, 2017;Méndez-Quintas et al, 2018), Italy (Pereira et al, 2015(Pereira et al, , 2018Voinchet et al, this issue) or France (Duval et al, submitted).…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 1 more Smart Citation
“…A multiple centre approach seems therefore indispensable when dating this type of fluvio-estuarine sediment, even when the sedimentological characteristics of the sediments seem initially quite suitable for an ESR study (as it was the case for the Tourville D1 and I units). Similar observations have been recently made on fluvial deposits from Spain (Duval et al, 2017;Méndez-Quintas et al, 2018), Italy (Pereira et al, 2015(Pereira et al, , 2018Voinchet et al, this issue) or France (Duval et al, submitted).…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…Previous cross-comparison studies showed good agreement with results derived from other numerical dating methods such as Luminescence, U-series and 40 Ar (e.g. Duval et al, 2017;Méndez-Quintas et al, 2018;Pereira et al, 2018). Unfortunately, given the very limited number of laboratories and researchers specialized in the ESR dating applications mentioned above, inter-laboratory comparison studies remain very rare.…”
Section: Accepted Manuscriptsupporting
confidence: 66%
“…Equivalent dose (D e ) values were determined for single quartz grains using the single aliquot regenerative dose (SAR) procedure 85 and only accepted for dating purposes if they satisfied a series of quality assurance criteria 86 . Single-grain D e measurements were made using the experimental apparatus described by Dumero et al 87 and Méndez-Quintas et al 88 after manually loading quartz grains into standard single-grain aluminium discs drilled with an array of 300 × 300-μm holes.…”
Section: Methodsmentioning
confidence: 99%
“…En este sentido tanto el yacimiento de Arbo como el de Porto Maior, con referencias cronológicas sólidas que los sitúan hacia los mis 8 y 6 respectivamente, constituyen ejemplos temporalmente avanzados del tecnocomplejo achelense, pero con paralelos en el contexto peninsular (Sánchez Cervera et al, 2015). La coexistencia de conjuntos achelenses y Paleolítico Medio antiguo dibuja un escenario cultural y posiblemente paleoantropológico mucho más complejo del que se desprendía de la tradicional visión gradualista sobre el proceso de cambio entre el Paleolítico Inferior y Medio, casi exclusiva en la investigación europea desde principios del s. xx (Chazan, 2009;Santonja et al, 2016).…”
Section: Conclusionesunclassified